Strengthening the Gatekeeper Function of Banks: The Role of KYC in Anti-Money Laundering Legal Framework - Efendi Lod Simanjuntak; Gautam Kumar Jha (Lex Publica, 2025)
This study critically examines the role of Know Your Customer (KYC) compliance within Indonesia’s anti-money laundering and counter-terrorism financing (AML/CFT) framework. Employing a normative juridical approach, the research analyzes key regulatory instruments, including Law Number 8 of 2010, POJK Number 12/POJK.01/2017, and the institutional role of PPATK, alongside relevant legal doctrines and international standards, particularly those of the Financial Action Task Force (FATF). The study addresses three core issues: the structuring of KYC obligations within Indonesia’s legal framework, the implementation of KYC principles by financial institutions as part of risk management strategies, and the challenges encountered in practice. The findings demonstrate that KYC functions as a central legal and operational instrument, enabling customer identification, transaction monitoring, and reporting of suspicious activities, thereby reinforcing the banking sector’s role as a gatekeeper in preventing financial crimes. However, its effectiveness is constrained by data quality issues, technological limitations, uneven institutional capacity, and increasingly sophisticated laundering techniques. The study concludes that strengthening regulatory enforcement, enhancing technological adoption (including RegTech and AI), and improving inter-agency coordination are essential to optimize KYC effectiveness.